2022
DOI: 10.3390/medicina58060694
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and Alarmins

Abstract: Schizophrenia, consisting of a group of severe psychiatric disorders with a complex etiology, is a leading cause of disability globally. Due to the lack of objective indicators, accurate diagnosis and selection of effective treatments for schizophrenia remain challenging. The association between schizophrenia and alarmins levels has been proposed for many years, but without solid evidence. Alarmins are prestored molecules that do not require processing and can be released upon cell death or damage, making them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 96 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…Schizophrenia, as a mental disorder, still lacks a well-characterized etiology. Research has defined it as a neurodevelopmental disorder with a complex genetic basis ( 1 , 2 ). Individuals with schizophrenia often exhibit cognitive dysfunction and negative symptoms that are frequently resistant to therapeutic interventions ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia, as a mental disorder, still lacks a well-characterized etiology. Research has defined it as a neurodevelopmental disorder with a complex genetic basis ( 1 , 2 ). Individuals with schizophrenia often exhibit cognitive dysfunction and negative symptoms that are frequently resistant to therapeutic interventions ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Huan Ma reviewed the topic of alarmin levels, including HMGB1, in schizophrenic patients, and he indicates that studies suggest strong links between the HMGB1 protein and schizophrenic disorders. The author of that paper indicates that HMGB1 levels were elevated in schizophrenic patients compared with healthy individuals [98]. Al-Dujaili et al demonstrated that serum HMGB1 levels were significantly higher in patients with schizophrenia than in a control group of healthy individuals [99].…”
Section: Hmgb1 In Psychiatrymentioning
confidence: 99%
“…Several lines of evidence have already shown a close association of ceRNA networks with several forms of cancer but very little is known for schizophrenia [32]. As substantial evidence of an altered immune landscape in schizophrenia has accumulated [33][34][35] and recent research has solidified the probable role of lncRNAs in orchestrating an altered immune landscape in the disease [36], we narrowed down the analysis to focus on identifying immune/ inflammatory signals by using a relevant expression dataset from publicly available database with the propensity to identify these peripheral signals, if any and performed bioinformatics analyses to highlight the lncRNA-associated ceRNA networks. It is hypothesized that such strategies may potentially reveal putative novel pathways and/or give credence to erstwhile proposed theories for disease etiology.…”
Section: Introductionmentioning
confidence: 99%